A study of clinical profile of neonates with respiratory distress and predictors of their survival admitted in neonatal intensive care unit of tertiary care hospital - Palod, Pushpak H.; Lawate, Bhagwat B.; Sonar, Mahesh N.; Bajaj, Sneha P. (International Journal of Contemporary Pediatrics, 2017)
Background: Respiratory disorders are the most frequent cause of admission for neonatal intensive care in both term and preterm infants. The clinical diagnosis of respiratory distress in a newborn is suspected if the respiratory rate is greater than 60 per minute in a quite resting baby, presence of grunting and/or there are inspiratory subcostal/intracostal retractions Signs and symptoms of respiratory distress include cyanosis, grunting, nasal flaring, retractions, tachypnea, decreased breath sounds with or without rales and/or rhonchi, and pallor. Objectives of present study were to know the clinical profile and aetiology of neonates with respiratory distress and to study the morbidity and mortality of respiratory distress in neonatal intensive care unit (NICU). And to find out the predictors of survival in the neonates admitted with respiratory distress. Methods: Study is done on 281 neonates admitted in Neonatal Intensive Care Unit (NICU) as a Prospective Cohort and Descriptive Study and Simple Random sampling is used to include neonates in the study. All the neonates included in study were subjected to the following detailed perinatal history and thorough clinical examination of newborns was done. Results: Males outnumber the females in admission. Most of the affected neonates were weighing between 1500g to 2500g (185). Out of total patients of two hundred and eighty-one, there were 35 deaths (12.5%) and 246 patients survived (87.5%). In present study most common causes for respiratory distress were respiratory distress syndrome (31.3%), neonatal septicaemia including pneumonia (28.1%), TTBN (16.7%). Conclusions: The overall survival rate was 87.5%. Male outnumber female on admissions but the survival in females was better than males. Common causes of respiratory distress in our study are RDS, Neonatal septicaemia and TTBN. As the gestation increased the survival also improved. Term neonates had better survival as compared to preterm neonates. Antenatal corticosteroid administration improved the survival.